The geology, petrology and geochemistry of the mineralization and hydrothermal alteration at Ongeama, Ongombo and Matchless West Extension, Namibia - Moroni, Marilena (Rhodes University, Faculty of Science, Department of Geology, 1991)
The Matchless Amphibolite Belt (Damara Orogen, Namibia) hosts several volcanogenic-exhalative, sediment-hosted stratiform cupriferous pyrite deposits. These are thought to be related to submarine volcanism during the early evolutionary stages of a narrow Damaran ocean, the Matchless Trough. The mineralized bodies examined (Ongeama, Ongombo and Matchless West Extension) are deformed and metamorphosed to low-medium grade (greenschist-amphibolite facies). They are associated with metapelite and amphibolite country rocks, and crop out as prominent limonite-rich gossans. The elongated shape of the sulphide bodies suggests a structural control. The mineralization normally consists of a variably developed massive sulphide portion, either quartz-, talc- or amphibole-bearing, and a stratigraphically overlying, extensive horizon of sulphide- and baryte-bearing exhalite (magnetite quartzite and less common talc- and actinolite-bearing schists). Lateral and vertical mineralogical changes within the mineralization match with significant variations in the element distribution. A metamorphosed and deformed alteration pipe, indicating the position of the fluid conduit, can be recognized in association with some ore bodies. The formation of quartz-muscovite and chlorite alteration envelopes (Ongeama, Matchless West Extension) and the presence of subtle mineralogical changes (Ongombo) in the immediate wallrocks, accompanied by extensive redistribution, leaching and introduction of elements from outside, suggest the hydrothermal metasomatic origin of the alteration zones. Element zoning within the mineralized bodies can be related to the original position of the vent, possibly coinciding with the intersection of the axis of the alteration pipe with the sulphide body. Cu, Zn, Au (pro parte) and Mo are enriched proximal to the vent, whereas Pb, Ba, Mn, Ag, Au, Sn, Bi and W enrichment characterizes the distal facies of the mineralization. In spite of the obliterating and disrupting effects of the regional dynamo-metamorphism, the element distribution within the mineralization and alteration zones examined is comparable with the geochemical trends observed in present-day mineralizing systems in early- stage oceanic environments (e.g. Guaymas Basin). During exploration for blind volcanogenic mineralization, the detection of hydrothermally altered rocks is fundamental in indicating the proximity to the mineralization. The localization of the alteration zone is also important in the interpretation of the regional geology of the explored area: in deformed terrains the assessment of the stratigraphic position of the alteration zone, relative to the mineralization, helps in establishing the polarity of the sequence.
Keywords: Geology -- Namibia; Petrology -- Namibia; Geochemistry -- Namibia